Abnormal Platelet Functions in a Patient with Abetalipoproteinemia - Surya, Ingrid I; Mommersteeg, Marlene; Gorter, Gertie; Willem Erkelens, D; Akkerman, Jan-Willem N (Thrombosis and Haemostasis, 1991)
Studies with isolated lipoproteins and washed platelets suggest that lipoproteins may affect platelet functions. We investigated platelet-rich plasma (PRP) from a patient with abetalipoproteinemia (ABL), whose plasma lacks apo-B containing lipoproteins (VLDL, LDL and chylomicrons). ABL-PRP aggregated poorly with different agonists and failed to respond to arachidonate. Thromboxane. B2 (T×B2) formation was severely impaired. After gel-filtration most of the aggregation defects persisted in agreement with reduced metabolism of endogenous arachidonate. However, arachidonate-induced aggregation and T×B2 production partially normalized. Normal platelets suspended in ABL plasma showed similar defects in aggregation and T×B2 production but arachidonate-induced aggregation was much lower than expected on the basis of T×B2. We conclude that the abnormal platelet functions in ABL-PRP are caused by (i) an intrinsic platelet abnormality due to reduced arachidonate mobilization and (ii) a property in ABL plasma that inhibits aggregation partially by trapping the arachidonate and partially by an unidentified mechanism. The latter properties may be the result of the abnormal lipid composition of ABl-plasma.